Sustaining zinc bioavailability in wheat grown on phosphorus amended calcisol. (November 2019) - Yousaf, Sundas; Akhtar, Muhammad; Sarwar, Nadeem; Ikram, Wasiq; Hussain, Saddam
Abstract: The deficiency of zinc (Zn) and phosphorus (P) occurs widely in alkaline calcareous soils, and the antagonism between these two elements is also a major cause of low Zn uptake in wheat, leading to low productivity and quality. The present study investigated the different methods of Zn application for wheat cultivars [i.e. Faisalabad-2008 (Fsd-08) and Zincol] grown on P amended calcisol. Data regarding yield component, estimated Zn bioavailability and phytate content in grain were recorded. Compared to zero P control, application of phosphoric acid (PA) and di-ammonium phosphate (DAP) to wheat cultivar Fsd-08 increased biological yield by 49.1 and 76.4%, grain yield by 45.5 and 43.1%, and grain-P by 79.2% and 25.6%, respectively. The Zn-treatment (irrespective of mode of its application) produced higher grain Zn content, however, application of PA and DAP decreased grain Zn concentration by 26.5 and 30.5%, respectively relative to zero P treatments. Almost similar trend was observed in Zincol cultivar in terms of increase in yield parameters and grain-P and Zn content of wheat. The phosphate application also affected phytate to Zn molar ratio (PZR) which was usually found lower in Zincol (range: 12–35) while higher in Fsd-08 (range: 12–43). Overall, PA application was found to have higher beneficial effects in terms of increasing yield parameters and grain-Zn in wheat cultivars. In crux, the current investigation suggests that Zn application; especially foliar sprays sustained higher grain content while Zincol cultivar in particular accumulated higher grain-Zn grown on calcareous soils applied with phosphate fertilizers. Graphical abstract: Zinc uptake, translocation and assimilation in wheat is significantly affected by phosphate application in alkaline calcareous soils. Other factors that may affect Zn availability in soil include plant factors (root exudates, ZIP family and DMA family Zn transporters, etc.) and soil factors (soil pH, organic matter, competitive cations and Soil P) while its bioavailability in grain greatly depends on phytate:Zn ratio. Image 1038922 Highlights: Zinc (Zn) application was evaluated for Zn bioavailability in wheat cultivars grown on phosphorus amended calcisol. Phosphoric acid was more effective than diammonium phosphate in enhancing crop yield and phytate content of wheat. Phosphorus application decreased grain Zn, and affected phytate: Zn ratio (PZR) which was lower in Zincol than Fsd-08. Foliar Zn-sprays significantly improved estimated Zn bioavailability in wheat grain under phosphorus amended calcisol.